Infrared Thermography to an Aluminium Foam Sandwich Structure Subjected to Low Velocity Impact Tests. (2016) - Meola, C.; Boccardi, S.; Petrone, G.; Boffa, N.D.; Ricci, F.; Carlomagno, G.M.
Abstract: This work is the straightforward continuation of previous ones in which vibro-acoustic characteristics of AFS panels were investigated both numerically and experimentally. Herein, the use of infrared thermography (IRT) is exploited to investigate impact damaging of an aluminium foam sandwich panel by monitoring its surface, opposite to the impact, during a low velocity impact test, which is performed with a modified Charpy pendulum. Thermal images, acquired in time sequence during the impact by the infrared camera, are post-processed to get information useful for understanding absorption capabilities and impact damaging mechanisms of this kind of structure.